Effects of exercise in people with multiple sclerosis: a systematic review and meta-analysis - Du, Liwen; Xi, Haoyu; Zhang, Shiyan; Zhou, Yilun; Tao, Xifeng; Lv, Yuanyuan; Hou, Xiao; Yu, Laikang (Frontiers in Public Health, 2024)
Background: A growing body of studies have examined the effect of exercise in people with multiple sclerosis (MS), while findings of available studies were conflicting. This meta-analysis aimed to explore the effects of exercise on balance, walking ability, walking endurance, fatigue, and quality of life in people with MS. Methods: We searched PubMed, Web of Science, Scopus, and Cochrane databases, through March 1, 2024. Inclusion criteria were: (1) RCTs; (2) included an intervention and control group; (3) had people with MS as study subjects; (4) had balance, walking ability, walking endurance, fatigue, or quality of life as the outcome measures. Exclusion criteria were: (1) non-English publications; (2) animal model publications; (3) review articles; and (4) conference articles. A meta-analysis was conducted to calculate weighted mean difference (WMD) and 95% confidence interval (CI). Cochrane risk assessment tool and Physiotherapy Evidence Database (PEDro) scale were used to evaluate the methodological quality of the included studies.Results: Thirty-five studies with a total of 56 exercise groups (n = 1328) and 41 control groups (n = 827) were eligible for meta-analysis. Exercise significantly improved BBS (WMD, 3.77; 95% CI,